Hubungan Antara Umur, Jenis Kelamin, Bentuk Tubuh, dan Kepercayaan Diri terhadap Perilaku Bullying pada Anak Usia Dini - Anggraeni, Dewi; Diana; Yuniarti (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Bullying has occurred among children in Indonesia at various levels of education, from high school, middle school, elementary school, and even early childhood education. Bullying in Indonesia has brought a lot of psychological and physical trauma. Following these problems, this research aims to determine the bullying behavior that occurs in young children in cities and villages along with the largest percentage of the types of bullying behavior that occurs. Apart from that, this research also tested the relationship between several children's characteristics, such as age, gender, body shape, and self-confidence on bullying behavior. This research method is descriptive quantitative and correlational with a sampling technique using cluster sampling. Research data collection used a survey method by distributing questionnaires to 4 PAUD schools in Pontianak City and 4 PAUD schools in Kubu Raya Regency. From the 172 data obtained, it shows that every child, both in the city and in the village, experiences all types of bullying behavior with the largest percentage being physical bullying. This research also shows that age, gender, and self-confidence have a significant relationship to bullying behavior. Based on the research results, participation from various parties is needed to prevent and deal with bullying problems that begin in early childhood who are entering the golden age. Not only in cities, bullying in villages also needs to be given more attention, because bullying incidents in villages have a higher percentage than in cities.